Treatment of postmenopausal osteoporosis patients with teriparatide for 24 months reverts forming bone quality indices to premenopausal healthy control values - Paschalis, Eleftherios P; Gamsjaeger, Sonja; Klaushofer, Klaus; Shane, Elizabeth; Cohen, Adi; Stepan, Jan; Pavo, Imre; Eriksen, Erik F; Taylor, Kathleen A; Dempster, David W (Bone, 2022)
Postmenopausal osteoporosis (PMOP) therapies are frequently evaluated by bone mineral density (BMD) gains against patients receiving placebo (calcium and vitamin D supplementation, a mild bone turnover-suppressing intervention), which is not equivalent to either healthy or treatment-naive PMOP. The aim of the present observational study was to assess the effects of TPTD treatment in PMOP (20 μg, once daily) at 6 (TPTD 6m; n = 28, age 65 ± 7.3 years), and 24 (TPTD 24m; n = 32, age 67.4 ± 6.15 years) months on bone quality indices at actively forming trabecular surfaces (with fluorescent double labels). Data from the TPTD-treated PMOP patients were compared with those in healthy adult premenopausal women (HC; n = 62, age 40.5 ± 10.6 years), and PMOP receiving placebo (PMOP-PLC; n = 94, age 70.6 ± 4.5 years). Iliac crest biopsies were analyzed by Raman microspectroscopy at three distinct tissue ages: mid-distance between the second label and the bone surface, mid-distance between the two labels, and 1 μm behind the first label. Mineral to matrix ratio (MM), mineral maturity/crystallinity (MMC), tissue water (TW), glycosaminoglycan (GAGs), and pyridinoline (Pyd) content were determined. Outcomes were compared by ANCOVA with subject age and tissue age as covariates, and health status as a fixed factor, followed by Sidak's post-hoc testing (significance assigned to p < 0.05). Both TPTD groups increased MM compared to PMOP-PLC. While TPTD 6m had values similar to HC, TPTD 24m had higher values compared to either HC or TPTD 6m. Both TPTD groups had lower MMC values compared to PMOP-PLC and similar to HC. TPTD 6m patients had higher TW content compared to HC, while TPTD 24m had values similar to HC and lower than either PMOP-PLC or TPTD 6m. Both TPTD groups had lower GAG content compared to HC group, while TPTD 6m had higher values compared to PMOP-PLC. Finally, TPTD 6m patients had higher Pyd content compared to HC and lower compared to PMOP-PLC, while TPTD 24m had lower values compared to PMOP-PLC and TPTD 6m, and similar to HC group. The results of the present study indicate that effects of TPTD on forming trabecular bone quality indices depend on treatment duration. At the recommended length of 24 m, TPTD restores bone mineral and organic matrix quality indices (MMC, TW, Pyd content) to premenopausal healthy (HC) levels.
Keywords: inhibitory kostní resorpce; Bone Density Conservation Agents; Postmenopausal osteoporosis; Humans; os ilium; lidé středního věku; Osteoporosis, Postmenopausal; Teriparatide; Female; Aged; dospělí; senioři; lidé; Ilium; Adult; ženské pohlaví; Raman spectroscopy; postmenopauzální osteoporóza; Middle Aged; Bone Density; Human iliac crest biopsies; kostní denzita; teriparatid; Bone formation; Bone quality